(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
In this article, a mathematical model of working fluid inlet into chamber of rotary expansion machine from source of superheated steam. The main practical problem that can be solved on the basis of this model is to determine dependence of torque on the angular velocity, i.e. in the construction of mechanical characteristics of rotary expansion machine.